Respostas
respondido por:
0
X²+1=7+X
X²+1-7-X=0
X²-X-6=O
Δ =b²-4.a.c
Δ =-1²-4.1.(-6)
Δ =1+24
Δ =25
x=-b+- √Δ x=1+-√25 x=1+-5 x1=1+5 x1=6 x1=3
--------- ---------- ------- ------ -----
2.a 2.1 2 2 2
x2=1-5 x2=4 x2=2
------ ------
2 2
X²+1-7-X=0
X²-X-6=O
Δ =b²-4.a.c
Δ =-1²-4.1.(-6)
Δ =1+24
Δ =25
x=-b+- √Δ x=1+-√25 x=1+-5 x1=1+5 x1=6 x1=3
--------- ---------- ------- ------ -----
2.a 2.1 2 2 2
x2=1-5 x2=4 x2=2
------ ------
2 2
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás